Die Herausbildung einer neuen Economic Governance als Strategie zur autoritären Krisenbearbeitung in Europa – gesellschaftliche Akteure und ihre Strategien - Konecny, Martin (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2012)
In the context of the economic crisis and the European sovereign debt crisis in particular the dominant social forces and state apparatuses are pushing for a long term solution. Here I argue that relevant European class forces as well as national class factions established the so called Six Pack as a political strategy that aims to radicalize neoliberal policies via European regulations. While in the member states democratic structures are being minimized, more decisions are made on the European level, through which the executive apparatus, especially the European Commission, gains more influence. I analyze the way in which the dominant social forces shaped the Six Pack and examine similarities but also differences to the European Fiscal Compact. Finally I look at the meaning of these current reforms for a left strategy of rupture in Europe.